Numerical classification of the Carici caryophylleae-Genistetea lobelii in Corsica (France) - Delbosc, Pauline; Le Dez, Mathieu; Bouzillé, Jean-Bernard; Cianfaglione, Kevin; Bioret, Frédéric (Mediterranean Botany, 2021)
Carici-Genistetea lobelii Klein 1972 corresponds to cyrno-sardinian oromediterranean cushion scrub and related grasslands. In France, this class is only present in Corsica and the syntaxonomic scheme is debated among phytosociologists. The aim of this paper is to highlight the main plant associations of Carici-Genistetea lobelii Klein 1972 and to define the diagnostic species for each phytosociological unit. We compiled 519 vegetation plots and we applied EuropeanVegetationChecklist expert system for the classes of European vegetation to retain only vegetation plots belonging to Carici-Genistetea lobelii. We obtained a dataset with 189 vegetation plots and we classified them with Modified TWINSPAN classification. Our analyses recognized 6 plant associations and 3 sub-associations already described in the literature; and to describe a new alliance corresponding to the supra-mediterranean vegetations (Genistion salzmannii), a new association (Brimeuro fastigiatae-Juniperetum nanae) and its sub-association (alnetosum suaveolentis). For each of them, we identified diagnostic, constant and dominant species and produced their distribution map. Formal definitions were then written for each phytosociological unit (from subassociation to class) and grouped in an expert system to automatically classify the vegetations of Carici-Genistetea lobelii.